Exploring the Compensation Plans Under International Laws from Offshore Oil Facilities and Relationship between Oil Production, Trade and Carbon Emission: An Evidence from Global Economy - Saboohi, Misbah (International Journal of Energy Economics and Policy, 2020)
The world dependency on oil is not diminishing. This article aims to sift through the liability rules applicable to oil spill accidents from offshore drilling. The discussion will explore the scope of compensation heads in offshore oil accidents e.g. employee deaths, community losses, related economic losses, natural resources damage. To find answers procedural issues such as class-tort claims need broad attention. The civil and criminal charges/penalty against the responsible parties in oil industry, and possible defense strategies, are also discussed theoretically. Additionally, this article offers some recommendations to re-invent international legal system for better protection of the environment by the offshore oil companies through better preparedness rules, stronger insurance system and efficient liability laws. Besides, this study has also explored the empirical relationship between crude oil production, trade and carbon emission in six different regions. Findings of the study providing the empirical evidence that in different region, production and trade of oil are primarily responsible for the increasing carbon emission in natural atmosphere. Such findings provide a significant evidence for both practical and managerial implications in the coming time. However, study is limited in terms of providing the empirical facts for only three indicators, while the factors like total energy production, energy intensity of GDP, oil products production, natural gas production and LNG production and their association with carbon emission is entirely missing which may address in future studies. Keywords: Marine environment; offshore oil company; Compensation; polluter pays principle, carbon emission, oil production, oil trade. JEL Classifications: J38, K33, O24 DOI: https://doi.org/10.32479/ijeep.9181